Nepal : Small Area Estimation of Poverty, 2011 - World Bank (Washington, DC, 2014)
Small area estimates of poverty have become useful tool in targeting poverty reduction by geographic areas. For Nepal, this is the second poverty map produced after a gap of seven years in collaboration with the Central Bureau of statistics, Nepal. This report presents 2010/11 small-area estimates and maps for Nepal at the 75 district, 967 ilaka and 2344 'target area' level, of poverty incidence, poverty gap, and poverty severity. The report also provides maps of the number of poor and their average consumption. As the newly introduced target areas are generally smaller than conventional aggregation levels, special attention is devoted to investigating the precision of the point estimates and to interpretation of the results. The poverty maps could usefully be expanded to other indicators of welfare such as nutrition and food security like in 2006. Detailed spatial distribution of poverty offers an opportunity to explore further the causes of poverty trends in Nepal. When combined with the spatial distribution of correlates of poverty such as access to roads, schools and health facilities, and other variable of economic geography, one can further our understanding of the persistence of pockets of poverty in Nepal. The present report updates the 2006 results for Nepal in three ways. First, it uses the recently published 2010/11 round of the Nepal Living Standards Survey (NLSS) and 2011 population census in order to produce an updated description of the spatial patterns of poverty. Second, it incorporates new methodological refinements aimed at improving modeling of the standard error. Third, in an effort to improve practical usability of the results, estimates are produced at the sub-ilaka or Village Development Committees (VDC) level - where possible-instead of sticking with the ilaka level that was used in 2006.